THE POTENTIAL OF CYCLING ACTIVITIES FOR PURPOSES OTHER THAN SPORTS AND RECREATION (CASE STUDY: BEFORE AND DURING THE COVID-19 PANDEMIC IN BANDUNG CITY) - Deca Syahputra, Wien
The use of bicycle transportation modes in Bandung has increased significantly during COVID-19 pandemic. This study aims to investigate the potential use of bicycles in the future for purposes other than sports and recreation, such as work. The study design adopts the principles of developing Non-Motorized Transportation (NMT) and bicycle mode choice literature which applied to data taken by questionnaire and observation. The analysis includes descriptive and spatial analysis, reliability test, association test, and binary logistic regression. Furthermore, the theory and principles adopted fulfill the principle of reproducibility and replicability in scientific methods, confirming the intial hypothesis that individual habits and attitudes affect willingness to bike in addition to socio-demographic, travel, and built-environmental characteristics. Moreover, factors influencing bicycle mode choice as shown by logistic regression results obtained at ? = 0,05 are that cycling for exercise and recreation is a positive factor before COVID-19 but will reduce individual probability of using it as the main mode of transportation during COVID-19. Next, cycling for work or school purposes is a strong positive factor in using a bicycle after COVID-19. It can be concluded that from the demand side, there is potential for the use of bicycles for other than sports, namely for work, school, and shopping purposes. However, if the supply side, such as bike facilities, regulations, and policies, falls short, the potential for sustainable bicycle use may disappear, reverting to the pre-COVID-19 condition, resulting in a minimal presence of cyclists in Bandung.